The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fnhum.2018.00121
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Multichannel EEG Patterns During Human Sleep: A Novel Approach

Abstract: Classic visual sleep stage scoring is based on electroencephalogram (EEG) frequency band analysis of 30 s epochs and is commonly performed by highly trained medical sleep specialists using additional information from submental EMG and eye movements electrooculogram (EOG). In this study, we provide the proof-of-principle in 40 subjects that sleep stages can be consistently differentiated solely on the basis of spatial 3-channel EEG patterns based on root-mean-square (RMS) amplitudes. The polysomnographic 3-chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 29 publications
2
31
0
1
Order By: Relevance
“…As has already been shown previously, it is possible to discriminate sleep stages solely on the basis of spatially distributed cortical activitypatternsbymeansofRMS amplitudes [9]. However, the potential of this methodology goes beyond the possibility of isolated sleep stage analysis.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…As has already been shown previously, it is possible to discriminate sleep stages solely on the basis of spatially distributed cortical activitypatternsbymeansofRMS amplitudes [9]. However, the potential of this methodology goes beyond the possibility of isolated sleep stage analysis.…”
Section: Discussionmentioning
confidence: 94%
“…These single values recorded across the different recording channels during the same time bin reflect a spatial pattern of neuronal activity present at that time. The complete method has been described previously elsewhere [8,9] but will be summarized here: The normalized RMS values of each single EEG channel were calculated for each 30 s epoch (synchronized to the sleep stage analysis). The RMS amplitudes of the three recording channels correspond to a three-dimensional vector for each 30 s interval, whereas successive vectors form a trajectory in three-dimensional space.…”
Section: Extracting Spatiotemporal Patterns Of Neuronal Activity Frommentioning
confidence: 99%
See 2 more Smart Citations
“…The cortical activity patters were represented by amplitude vectors calculated via a sliding window method (for the exact procedure see [14]). We could already demonstrate that this method enables to discriminate different sleep stages in human EEG recordings [16]. Furthermore, we could analyze the microstructure of cortical activity during sleep and found that it reflects respiratory events and state of daytime vigilance [17].…”
Section: Introductionmentioning
confidence: 94%